Accuracy and reliability of pulse O2 saturation measured by a wrist-worn oximeter - Hermand, E.; Coll, C.; Richalet, J.-P.; Lhuissier, F. J. (International Journal of Sports Medicine, 2021)
This study aims to evaluate the accuracy of the Garmin Forerunner 245 heart rate (HR) and pulse O2 saturation (SpO2) sensors compared with electrocardiogram and medical oximeter, from sea level to high altitude. Ten healthy subjects underwent five tests in normoxia and hypoxia (simulated altitudes from 3000 to 5500 m), consisting in a 5-min rest phase, followed by 5-min of mild exercise. Absolute error (±10 bpm for HR and ±3% for SpO2, around criterion) and intraclass correlations (ICC) were calculated. Error rates for HR remained under 10%, except at 3000 m, and ICCs evidenced a good reliability between Garmin and criterion. Overall SpO2 was higher than criterion (P<0.001) with a >50% error rate (>80% above 4800 m), and a poor reliability with criterion. The Garmin device displayed acceptable HR data at rest and exercise for all altitudes, but failed to provide trustworthy SpO2 values, especially at high altitude, where a pronounced arterial O2 desaturation could lead to acute mountain sickness in hypoxia-sensitive subjects, and its life-threatening complications; moreover, readings of overestimated SpO2 values might induce trekkers into further hazardous behavior by pursuing an ascent while being already at risk. Therefore, its use to assess SpO2 should be proscribed in altitude for acclimatization evaluation.